PENGARUH LOCUS OF CONTROL TERHADAP KONFLIK PERAN DAN AMBIGUITAS PERAN DENGAN ETIKA KERJA ISLAMI SEBAGAI VARIABEL ANTARA (STUDI PADA BANK JATENG KANTOR CABANG PEMBANTU JOHAR) - Hamdani, Muliawan (PRESTASI, 2014)
Abstract This research was conducted at the scope of Johar Subsidiary Branch Office of Bank Jateng, a subsidiary branch office of Bank Jateng which is located in the city of Semarang. The aims of this research were (1) to test empirically the influence of Locus of Control to the Role Conflict with Islamic Work Ethics as intervening variable. (2) to test empirically the influence of Locus of Control to the Role Ambiguity with Islamic Work Ethics as intervening variable. (3) to test empirically the difference of impregnability in Islamic Work Ethics upholding among internalizer type and externalizer type of employees. (4) to test empirically the influence of Islamic Work Ethics to the Role Conflict. (5) to test empirically the influence of Islamic Work Ethics to the Role Ambiguity. The population and samples of this research were 20 employees of Johar Subsidiary Branch Office of Bank Jateng. They all believe in Islam. The data of the research were obtained by questionnaires, literature study, and documentation. Later, to the questionnaires of the research, validity and reliability tests were conducted. Through both tests conducted, all criterions could be fulfilled. To test the validity of each hypothesis, regression and path analysis were applied. Based on both analysis, several conclusions were formulated. They were: (1) Locus of Control influenced the Role Conflict with Islamic Work Ethics as intervening variable (Hypothesis 1was accepted). (2) Locus of Control did not influence the Role Ambiguity with Islamic Work Ethics as intervening variable (Hypothesis 2 was rejected). (3) The employees with internalizer type did not perform the difference of impregnability in Islamics Work Ethics upholding with the externalizer type one (Hypothesis 3 was rejected). (4) Islamic Work Ethics influenced the Role Conflict (Hypothesis 4 was accepted). (5) Islamic Work Ethics did not influence the Role Ambiguity (Hypothesis 5 was rejected). Key Words: Locus of Control, Islamic Work Ethics, Role Conflict, and Role Ambiguity.